P5 ACCELERATION IN MADRASAH: STRATEGIC INTEGRATION OF THE TRI-DIMENSIONAL HARMONY MODEL IN THE INDEPENDENT CURRICULUM - Iskandar Iskandar; Mauhibur Rokhman; Muhammad Anas Ma’arif (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to analyze the acceleration of the Pancasila Student Profile Strengthening Project (P5) through the implementation of the Tri-Dimensional Harmony model (Theo-Synergy, Socio-Nationalist, and Managerial-Harmonious). The research method used is descriptive qualitative with a case study approach. Data were collected through participant observation, in-depth interviews with the facilitator team, and documentation of the project modules. The results showed that the Tri-Dimensional Harmony model successfully integrated Islamic spiritual values with Pancasila character systematically through three strategic steps: redesigning modules based on the integration of Kauniyah verses, forming a collaborative interdisciplinary facilitator team, and implementing Civic-Religious Engagement as a form of concrete community action. These findings proved that harmonization of managerial aspects and religious substance can increase the effectiveness of achieving student profile dimensions without obscuring the institutional identity. The implications of this study emphasized the importance of contextual curriculum orchestration for Islamic-based schools to accelerate the achievement of the Independent Curriculum targets. This model can be a managerial reference for similar educational institutions in managing character projects that were holistic, measurable, and have a wide impact.